2003
DOI: 10.1034/j.1600-0587.2003.02942.x
|View full text |Cite
|
Sign up to set email alerts
|

Forest fire history in Norway: from fire‐disturbed pine forests to fire‐free spruce forests

Abstract: I have used occurrence of macroscopic charcoal particles, pollen analyses and radiocarbon datings to examine local forest fire abundance in southern and central Norway. Peat cores, covering the last 1000 to 6000 yr, were sampled from 20 bog margin and swamp forest sites, and the charcoal records documented local fire occurrence in 10 of the sites. Forest fires have not occurred in the sites located in central Norway, whereas the fire occurrence in southern Norway showed large variation among the sites. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 27 publications
(41 reference statements)
5
40
0
1
Order By: Relevance
“…Pine forests have a fire return interval of 20-100 years (Zackrisson, 1977;Engelmark, 1984;Niklasson and Drakenberg, 2001). The fire return interval in spruce forests is much longer and can vary from a few hundred to several hundred years (Ohlson et al, 1997;Ohlson and Tryterud, 1999) or fires may even be totally absent (Tryterud, 2003).…”
Section: Spruce Versus Pine Forestsmentioning
confidence: 99%
“…Pine forests have a fire return interval of 20-100 years (Zackrisson, 1977;Engelmark, 1984;Niklasson and Drakenberg, 2001). The fire return interval in spruce forests is much longer and can vary from a few hundred to several hundred years (Ohlson et al, 1997;Ohlson and Tryterud, 1999) or fires may even be totally absent (Tryterud, 2003).…”
Section: Spruce Versus Pine Forestsmentioning
confidence: 99%
“…Data on fire frequencies were obtained from more than 70 fossil charcoal records from anthropogenic coastal Calluna heathlands (reviewed in [9,11,[13][14][15]) and 12 records from boreal-zone Calluna habitats [22][23][24][25]. From each study population, infructescences from 15 Calluna plants were harvested, dried at 208C for 2 days and stored for five months at 15% relative humidity and 158C.…”
Section: Methodsmentioning
confidence: 99%
“…Natural fire frequencies in these boreal habitats vary considerably in space and time but are much lower than those of the managed coastal heathlands [22][23][24][25]. To evaluate evolutionary impacts of the anthropogenic fire regimes, we assessed germination responses to smoke of Calluna seeds [9,11,13 -15]).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies of past fire regimes for northern Europe, climate was identified as the main driver [e.g., Pitkänen et al, 2002;Carcaillet et al, 2007;Olsson et al, 2010], but in addition to direct climate effects, interactions with species composition can also be important [Pitkänen et al, 2002;Tryterud, 2003;Brown and Giesecke, 2014]. A historical example of this is the (re-)establishment of spruce in Scandinavia during the Holocene, which is thought to be initiated by climate, and which could then trigger a change from a (prespruce) fire-prone to a (postspruce) fire-free area [Tryterud, 2003;Ohlson et al, 2011]. Observations such as these pose the question whether future climate change would also potentially lead to changes in natural vegetation types that could notably alter the future fire regime.…”
Section: Northern Europe: Will Changes In Vegetation Composition Matter?mentioning
confidence: 99%